Anaesthetic Management of Liver Resection Surgery in Birendra Army Hospital - KC, Nagendra Bahadur; Rai, Sashi; Panta, Sunita (Medical Journal of Shree Birendra Hospital, 2010)
This is a case report of a 65 yrs old male patient who underwent resection of left lateral segment (segment 2-3) of Liver for advanced Hepatocellular carcinoma. The case was performed under general anesthesiacombined with epidural analgesia for post op pain management. During resection, Hypotension ismaintained to reduce bleeding.Key words: Blood and CVP pressure; Epidural analgesia; General Anesthesia; Hepatocellular carcinoma(HCC); left lateral segmentectomyDOI:  10.3126/mjsbh.v9i1.3487Medical Journal of Shree Birendra Hospital Vol.9(1) 2010 24-27